Quelques textes inédits en vieux berbère provenant d’une chronique ibāḍite anonyme - Lewicki, Tadeusz (Revue des Études Islamiques, 1935)

Monnaies de la période idrisite trouvées à Volubilis - Colin, Georges Séraphin (Hespéris, 1935)
Keywords: Numismatique – Tahert

Empoisonnement d'une famille indigène par "Datura Metel" (solanacées), M’zab - Garnier, L. (Archives de l'Institut Pasteur d'Algérie, 1935)
Keywords: Médecine – Mzab

Despois (J.). — Le Djebel Nefousa (Tripolitaine). Etude géographique. - Blanchard, Raoul (Revue de Géographie Alpine, 1935)
Keywords: Recension

Deux ouvrages sur la Libye italienne - Bernard, Augustin (Annales de Géographie, 1935)
Keywords: Recension

Le culte du bélier dans la Tunisie musulmane - Lewicki, Tadeusz (Revue des Études Islamiques, 1935)
Keywords: Moeurs et coutumes – Afrique du Nord

DESPOIS (Jean). — Le Djebel Nefousa (Tripolitaine). Étude géographique. Paris, Larose, 1935. In-8°, 349 p., 29 fig., 17 pl., 3 cartes h. t. Hom. de l'édit. - Dubuc, E. (La Géographie, 1935)
Keywords: Recension

The Donatist Circumcellions - Beaver, R. Pierce (Church History, 1935)
Donatism was an exclusively African schism and for more than a century held the center of the stage in the Christian life of that land. It was born of local passions and quarrels, and had no success outside of Africa. It became the church of the native population and, raising“altar against altar,” 1 successfully opposed both the Catholic church and the Roman Empire during several generations. Frequently, and especially in Numidia, the church of Donatus was more numerous, richer, and more powerful than its Catholic neighbor. Moreover, the Donatist cause came to shelter under its name a true social and economic revolt, which it found a useful instrument at times, but which was never a recognized part of its policy. Although the Donatist controversy was thus a local schism, it had important results for the Latin church, chiefly in regard to the doctrine of the sacrament of baptism, the orders and reception of schismatics and heretics, and the coercion of non-Catholics.
Keywords: Donatisme

Ancora la presunta lettera di Shekib Arslan (Oriente Moderno, 1935)
Keywords: Réformisme

Presunta lettera dell’Emiro Shekib Arslan al Mufti Amin el-Huseini (Oriente Moderno, 1935)
Keywords: Réformisme

Polemiche fra giornali palestinesi agli articoli dell’Emiro Shekib Arslan sull’Italia (Oriente Moderno, 1935)
Keywords: Réformisme

Articoli dell’Emiro Shekib Arslan sulle relazioni italo-abissine e sul suo attaggiamento verso l’Italia (195-198) (Oriente Moderno, 1935)
Keywords: Réformisme

Ẓufār in the Middle Ages - Guest, R. (Islamic Culture, 1935)
Keywords: Dhofar

Nādir Shāh's Campaigns in 'Omān, 1737-1744 - Lockhart, Laurence (Bulletin of the School of Oriental and African Studies, 1935)
Keywords: Vie politique – Oman – 1624-1742

فرقة الخوارج - عز الدين, فريد مصطفى (الرسالة, 1935)
Keywords: Kharijisme

En excursion à Djerba (L'Afrique du Nord illustrée, 1935)
Keywords: Récits de voyage – Djerba

Political Theology in Early Islam: Ḥasan Al-Baṣrī's Treatise on Qadar - Obermann, Julian (Journal of the American Oriental Society, 1935)

Italian colonization in Libya : The Jebel Nefusa (The Geographical Review, 1935)
Keywords: Italie – colonies

Gli Ibaditi - Crocetta, Anchise (Bollettino del Governo della Libia, 1935)

Terre mozabite - Gers, José (Les feuillets bleus, 1935)
Keywords: Récits de voyage – Mzab